Civil Dispute Resolution in Environmental Pollution Cases: A Study on the Implementation of Sustainable Development Goals 13 - Meitadewi, Ni Made Putri (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The resolution of civil disputes in environmental pollution cases is a crucial issue in achieving environmental justice and sustainable development. Environmental pollution that causes harm to communities demands an effective, fair, and sustainable dispute resolution mechanism.Purposes of the Research: This study aims to analyze how the implementation of civil dispute resolution in environmental pollution cases aligns with the Sustainable Development Goals (SDGs) Goal 13, which focuses on climate action.Methods of the Research: The research employs a normative juridical approach with case studies and qualitative analysis, collecting data through literature review and documentation of court decisions.Findings of the Research: The findings reveal that mechanisms such as mediation, civil lawsuits, and class actions have been utilized in certain cases; however, they have not fully reflected ecological justice principles or ensured sustainable environmental recovery. The implementation of SDG 13 in dispute resolution remains partial and has yet to become a central legal guideline. Strengthening regulations and legal awareness that support preventive and restorative approaches is necessary to improve the handling of environmental pollution disputes. This study concludes that synergy between environmental civil law and the principles of SDG 13 must be enhanced to develop a dispute resolution system that not only resolves conflicts but also contributes to long-term environmental protection and restoration.